A new model of severe neurogenic pulmonary edema in spinal cord injured rat - Šedý, Jiří; Urdzíková, Lucia; Likavčanová, Katarína; Hejčl, Aleš; Jendelová, Pavla; Syková, Eva (Neuroscience letters, 2007)
We describe a new model of neurogenic pulmonary edema in spinal cord injured Wistar male rats. The pulmonary edema was elicited by an epidural thoracic balloon compression spinal cord lesion, performed under a low concentration of isoflurane (1.5 or 2%) in air. Anesthesia with 1.5% isoflurane promoted very severe interstitial and intraalveolar neurogenic pulmonary edema with a significantly increased thickness of the alveolar walls and massive pulmonary hemorrhage. In this group, 33% of animals died. Anesthesia with 2% isoflurane promoted severe interstitial and intraalveolar neurogenic pulmonary edema with less thickening of the alveolar walls and pulmonary hemorrhage. For evoking severe neurogenic pulmonary edema in spinal cord injured rats, 2% isoflurane anesthesia would be more suitable. However, if very severe neurogenic pulmonary edema needs to be evoked, spinal cord injury under 1.5% isoflurane anesthesia could be used, but one-third of the animals will be lost.
Keywords: poranění míchy; Animals; isofluran; Dose-Response Relationship, Drug; potkani Wistar; financování organizované; Isoflurane; zvířata; Disease Models, Animal; anestetika inhalační; Spinal Cord Injuries; Financing, Organized; Anesthetics, Inhalation; vztah mezi dávkou a účinkem léčiva; Rats; Male; Rats, Wistar; Pulmonary Edema; krysa rodu Rattus; mužské pohlaví; modely nemocí na zvířatech; plicní edém